Relationship between parenting styles and mental health in first-year university students - Sutrisno, Ananda Prastuti; Komala, Ratna (Science Midwifery, 2025)
This study examined the relationship between parenting styles and mental health among first-year university students in Indonesia. An analytic observational design with a cross-sectional approach was used. The research was conducted at two academies under Education Foundation X in Jakarta and included 43 first-year students aged 18–19 years who completed the Parental Authority Questionnaire-Short (PAQ-S) and the Depression, Anxiety, and Stress Scale-21 (DASS-21). Parenting styles were classified as authoritative, authoritarian, or permissive, and mental health was assessed in terms of depression, anxiety, and stress. Descriptive analysis showed that students who perceived their parents as authoritarian had the highest proportions of severe and extremely severe symptoms in all three domains. Non-parametric tests indicated significant differences in depression, anxiety, and stress scores across parenting style groups, with the authoritarian group showing higher median scores than the authoritative group. Post hoc comparisons confirmed that authoritarian parenting was associated with significantly poorer mental health than authoritative parenting. These findings suggested that parenting style remained an important factor for psychological well-being in late adolescence and supported the promotion of more authoritative parenting to help protect first-year university students from mental health problems.